2021
DOI: 10.1021/acscatal.1c03888
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-Catalyzed Enantioselective C–H Borylation of Diarylphosphinates

Abstract: P-stereogenic phosphorus compounds are a ubiquitous and critically important class of chiral ligands in asymmetric catalysis. Methods for catalytic asymmetric synthesis via a step- and atom-economic way are still very limited. We herein disclose a protocol of phosphinate-directed iridium-catalyzed enantioselective ortho-H borylation to construct P-stereogenic phosphorus compounds. A number of functional groups could be well tolerated to afford optically active diarylphosphinates with good to excellent enantios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 69 publications
1
14
0
1
Order By: Relevance
“…This work provided an approach for the synthesis of P-stereogenic phosphorus compounds through enantioselective borylation of meta-aryl C À Hb onds.V ery recently,X ua nd co-workers reported the synthesis of this type of compound through enantioselective borylation of ortho-aryl CÀHb onds,i nw hich iridium catalysts containing an N,B-ligand were used. [46] In contrast to the rapid development of iridium catalysts for the enantioselective borylation of CÀHb onds,h ighly enantioselective rhodium catalysts for the borylation of CÀH bonds are rare.T he first enantioselective borylation of CÀH bonds catalyzed by rhodium was reported by Sawamura in 2017 (Figure 31). [36] They showed that the combination of ar hodium precursor and ap hosphoramidite ligand led to enantioselective borylation at methylene CÀHb onds of saturated nitrogen heterocycles bearing ap yridyl group on nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This work provided an approach for the synthesis of P-stereogenic phosphorus compounds through enantioselective borylation of meta-aryl C À Hb onds.V ery recently,X ua nd co-workers reported the synthesis of this type of compound through enantioselective borylation of ortho-aryl CÀHb onds,i nw hich iridium catalysts containing an N,B-ligand were used. [46] In contrast to the rapid development of iridium catalysts for the enantioselective borylation of CÀHb onds,h ighly enantioselective rhodium catalysts for the borylation of CÀH bonds are rare.T he first enantioselective borylation of CÀH bonds catalyzed by rhodium was reported by Sawamura in 2017 (Figure 31). [36] They showed that the combination of ar hodium precursor and ap hosphoramidite ligand led to enantioselective borylation at methylene CÀHb onds of saturated nitrogen heterocycles bearing ap yridyl group on nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…This work provided an approach for the synthesis of P‐stereogenic phosphorus compounds through enantioselective borylation of meta ‐aryl C−H bonds. Very recently, Xu and co‐workers reported the synthesis of this type of compound through enantioselective borylation of ortho ‐aryl C−H bonds, in which iridium catalysts containing an N,B‐ligand were used [46] …”
Section: Enantioselective Borylation Of C−h Bondsmentioning
confidence: 99%
“…In 2021, Ke, Xu, and co-workers demonstrated an Ir(I)catalyzed enantioselective C-H borylation of diarylphosphinates 66 using the chiral bidentate boryl ligand (CBL) L23 as a chiral ligand (Scheme 23). 50 Borylated phosphorus compounds 68, substituted with a variety of functional groups, were obtained in up to 92% ee. Surprisingly, when the iso-hexafluoropropyl group in substrate 66 was changed to trifluoroethyl, the ee value of the product reduced dramatically to 66%, and even lower ee values were obtained by using simple alkyl diarylphosphinates, indicating that the fluorinated alkoxy moiety was essential for acquiring high enantioselectivity.…”
Section: Special Topic Synthesis 6 Ir(i)/chiral Bidentate Boryl Ligandmentioning
confidence: 99%
“…Owing to the useful attribute of C−B bonds, the development of regio‐ and enantioselective C−H borylation [18] could not only offer new types of chiral N−C axis but also expand the chemical space of axially chiral molecules. We herein disclose the first example of iridium‐catalyzed asymmetric C−H borylation using a chiral bidentate boryl ligand ( CBL ) [18a–j] to afford axially chiral N ‐aryl phthalimides with high enantioselectivities (Scheme 1B). We also demonstrated synthetic utility on a gram‐scale reaction for a variety of C−B bond transformations, including iterative dual C−H activation and the preparation of a chiral N ‐oxide catalyst for asymmetric catalysis.…”
Section: Introductionmentioning
confidence: 99%